Efektifitas Terapi Kelompok Suportif Ekspresif Dalam Menurunkan Depresi Depresi pada Orang Dengan HIV/AIDS - Cahyamita, Tisna; , Dr. Lisnawati Ruhaena, M.Si, Psi; , Wisnu Sri Hertinjung, S.Psi (2015)
Depression is a mental disorder most often occurs in patients with terminal diseases, including HIV/AIDS. It affect the readiness of patients treatment, so it is necessary to give psychological interventions for depression PLWHA such as supportive expressive (SE) group therapy. The purpose of this study is want to know the effectiveness of SE group therapy to reducing depression in PLWHA. The hypothesis is : 1). The rates of depression in experimental is defferent than control groups; 2). The rates of depression in the experimental group before treatment is defferent than after treatment. This experimental study using a quasi experimental pre-post test with control group treated with group therapy SE. Subject are 22 patients with HIV / AIDS, who experience moderate to high depression, measure with BDI scale, divided into two groups : 11 in the experimental group and 11 control group. The first hypothesis test results by Mann Whitney-U test showed the value of z count -3.779, significance level is 0.000, showed the rates of depression in experimental is significantly defferent than control groups.The second hypothesis test results with the Wilcoxon test showed the value of z -2.936, significance level is 0.003, showing the rates of depression in the experimental group before treatment is significantly defferent than after treatment. SE group therapy proved effective in reducing depression PLWHA. The rate depression of PLWHA is moderate to high. The main symptoms are grouped into two: anger and guilt.